Zakat management education : studies in UiTM campus of Puncak Alam / Nur Syafiqah Mohamad Saparudin - Mohamad Saparudin, Nur Syafiqah (Academy of Contemporary Islamic Studies (ACIS), 2016)
People often questioned about the excess millions undistributed zakat funds to recipients. The excess zakat grow tremendously from year to year. Arises a few question of the effectiveness of zakat distribution at the present time. It is difficult for the zakat central to manage the number of applications each year. This is because the major problem faced by the agency is the lack of manpower in the collection and distribution of zakat to identify the relevant IPT across the country. Accordingly, the involvement of IPT as agents of distribution and collection of zakat seen among the best alternative to solve this problem. zakat center can put the responsibility of collecting and distributing zakat among staff and university students to IPT zakat central. Indirectly it help zakat central to identify the recipients throughout the region in their respective states with a more efficient and comprehensive, in addition to optimizing the function of central zakat limited staff. The guidelines has been set by the central charity, for every student who applies charity they have through a strict screening process before being approved to receive zakat. It is not intended to make it difficult for students, but to know the background of the applicant including family circumstances and avoid the occurrence of fraud. Thus, this paper will discuss the operation of zakat collection among employees UiTM Puncak Alam campus and how screening is done by the management of zakat in determining which students are eligible to receive aid. Moreover, what the items and packages are available for students who are eligible to receive zakat aid in UiTM Puncak Alam campus. And what are the challenges faced by central zakat during carries out tasks as Amil at UiTM. Interviews were been done to central the head unit to answer the question related to UiTM zakat issues and solve the problems faced by the Zakat Central. Hence, the aims of this paper are to discuss in detail about the problem statement to answer some of these issues.